Gold Craftsmanship and Competitive Advantage: A Porter’s National Diamond Analysis of Azerbaijan’s Jewelry Industry - Mirzabayov, Azar (ADA University, 2025)
Azerbaijan's economy is heavily dependent on oil and gas production, and the government and policymakers have emphasized diversifying the economy into non-oil sectors and reducing petroleum dependency. According to this, on 19 September 2018, the President of the Republic of Azerbaijan acknowledged an order to support competitive domestic production in the non-oil sector. Reasons behind this decision, dependency on oil is not sustainable and any fluctuation in the price can negatively affect the economy of the country. The gold jewelry industry is one of the essential nonoil sectors for Azerbaijan’s economy that newly discovered gold resources are able to cover the needs of the industry (Valiyev, et al. 2023). This study examines the competitive dynamics and development potential of Azerbaijan’s gold jewelry industry within the context of the country’s broader economic diversification goals. Applying on Porter’s National Diamond model analyzing four key determinants, factor conditions, demand conditions, related and supporting industries and firm strategy, structure and rivalry, additionally, comparative case analysis of leading exporter countries such as Italy, India and Turkey. Primary data were collected by online consumer survey, supplemented by secondary resources such as stakeholders’ interviews on newspapers, government reports, industry publications and trade statistics. Outcomes show that Azerbaijan has significant natural resources and rich artisanal heritage, supported by training program and transport infrastructure. Strong domestic demand driven by cultural tradition and rising investment motives, coexists with growing local market share, yet global exports remain modest. Underdeveloped gemological and hallmarking systems, restricted access to cutting-edge production technologies, a lack of professionally trained designers, and inexperienced branding and quality-control frameworks are some examples of critical gaps. The effectiveness of cluster-based production, strong institutional support, and coordinated marketing initiatives in benchmark countries is highlighted by comparative analysis. The study suggests a multipronged approach to transform Azerbaijan's industry from a specialized regional player to a competitive worldwide exporter in light of these findings. The following are some of the main suggestions: creating regulated secondary gold markets and buying cooperatives; expanding design and vocational training; providing assistance for shared access to state-of-the-art equipment; implementing thorough hallmarking and gem-testing procedures; developing "Made in Azerbaijan" as a unique heritage brand; and supporting specialized clusters for design, manufacturing, and export promotion. By strengthening each aspect of the Diamond, these actions hope to spur innovation, raise standards, and open up new export markets.
Keywords: Gold jewelry industry -- Azerbaijan.; Jewelry trade -- Azerbaijan.; Economic diversification -- Azerbaijan.; Non-oil sector -- Azerbaijan.; Industrial clusters -- Azerbaijan.